The Training of Physics Olympiad for Students at SMA IT Al-Auliya Balikpapan - Shoodiqin, Dian Mart; Febrian Dedi Sastrawan; Meidi Arisalwadi; Atut Reni Septiana; Rahmania (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2023)
The Capital City of Indonesia will be moved from Jakarta to Penajam Paser Utara, East Kalimantan. Balikpapan, as the nearest big city from Penajam Paser Utara, has a huge potential in the development of science and technology in the future. However, achieving greater potential requires dedication, effort and hard work. Through this community service activity, it is expected that the enthusiasm of the young generation, especially high school students, related to the world of science (Physics) will increase. In this activity, the community engagement team provides a training regarding problem solving to physics olympaid question. Lecturing (material enrichment) and group discussion (answering examples of Physics Olympiad questions) methods were used in this activity. The result shows that the students’ ability in problem solving skill increased. It can be seen from the pre-test and post-test scores. Furthermore, one of the trained students won the competition in city level, Balikpapan City, and had a chance to join the competition in province level. Based on the result, Balikpapan's young generation has an enermous potential to develop science and technology. Hopefully, in the future this activity can be held in a wider and sustainable scope.